EFEKTIVITAS RELAKSASI BENSON DAN TEKNIK GUIDED IMAGERY TERHADAP KECEMASAN PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS: STUDI LITERATUR - Claudius Kevin; Hany Wihardja (Journal of Health Science and Physiotherapy, 2022)
ABSTRACT Chronic kidney disease is a long-lasting, gradual, and progressive decrease of kidney function. The therapy that can be given to patients with chronic kidney disease is hemodialysis. The continuous dan long process of hemodialysis makes patients tired, bored, anxious and even depressed. The aim of this literature study is to conduct a systematic review of research articles that evaluate the effectiveness of Benson Relaxation and Guided Imagery Techniques on Anxiety in Chronic Kidney Failure Patients Underwent Hemodialysis. The method used is literature review in the form of secondary analysis through scientific database portals such as Google Scholar and Science Direct published in 2015-2021 both national and international articles. The article search process uses keywords in English and Indonesian such as chronic kidney diseases, hemodialysis, anxiety, Benson relaxation and guided imagery technique. Based on the search results, 4.489 articles were found and then selected using inclusion and exclusion criteria and the PICOS format to become 10 articles from 2 countries, Indonesia and Iran. Benson’s relaxation and guided imagery made respondents feel relaxed and calm. Benson relaxation and guided imagery as non-pharmacological therapies need to be applied by hemodialysis nurses to reduce anxiety levels in chronic kidney diseases underwent hemodialysis because both therapies do not cause side effect in patients.